Statistical tests to reveal the nature of the relationship between public Expenditures, spending on health, education, and investment Expenditures during the period (2005-2020) - Hayder Sabah Tuama; Ali Salman Tuama Alchaabawi (Peerian Journals Publishing, 2023)
Increasing government spending is an inherent characteristic of rentier economies to which the theory (curse of resources) applies. In times of financial abundance, public spending increases and the state is obligated to its citizens. When crude oil prices fall, public spending decreases and affects spending on health, education and investment spending, proportionately. Expenditure, so conducting statistical and standard tests to reveal the nature of the relationship between the expenditures provided by the state and the amount of flexibility in change and impact on people's lives, in addition to showing the nature of public spending, the research focused on the size, type and nature of the state's role in spending, the researchers used a set of tests To get to know the reality of government spending in Iraq and its impact on the Iraqi reality, and it was found that there is a strong correlation between public spending and spending on health, education and investment spending, and the correlation was positive and direct. between investment spending and public spending
Keywords: Public Spending; Spending on Health; Spending on Education